2018
DOI: 10.3889/oamjms.2018.180
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Sunlight and Artificial UV Radiation Versus Chlorine for the Inactivation of Cryptosporidium Oocysts: An in Vivo Animal Study

Abstract: BACKGROUND:Cryptosporidium is an important waterborne protozoan.AIM:The aim of this study was to investigate the effect of sunlight being the natural source of UV and artificial UV irradiation on Cryptosporidium oocysts versus the effect of chlorination, being the traditional method of water disinfection and to provide an insight into the viability and degree of infectivity of Cryptosporidium oocysts, using an animal model.METHODS:An experimental study including 300 neonatal mice was carried out to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Since all three pathogens discussed in this review are transmitted via cysts [100], the prevention is water treatment by filtration [101] or disinfection by chlorination or radiation [102]. Moreover, person-to-person and animal-to-person transmission can be prevented by standard attention to hygiene (i.e., hand washing).…”
Section: Control and Treatmentmentioning
confidence: 99%
“…Since all three pathogens discussed in this review are transmitted via cysts [100], the prevention is water treatment by filtration [101] or disinfection by chlorination or radiation [102]. Moreover, person-to-person and animal-to-person transmission can be prevented by standard attention to hygiene (i.e., hand washing).…”
Section: Control and Treatmentmentioning
confidence: 99%
“…Also, the reduction of Cryptosporidium from effluents was inefficient by using chlorine disinfection and by trickling filter [11]. Moreover, UV irradiation and ultrafiltration as tertiary treatment processes were able to reduce Cryptosporidium oocysts in secondary effluents [46,47]. The importance of efficient wastewater treatment is to protect water bodies that receive the treated wastewater effluents from pathogen transmission [11].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that these pathogens, which include many forms of protozoa (such as Cryptosporidium parvum and Acanthamoeba spp.) and bacterial spores (such as Bacillus subtilis spores) are also more likely to resist conventional disinfection processes such as chlorination and ozonation [81,82]. Although SODIS has proven its ability to inactivate or considerably reduce the viability of most important and common waterborne disease such as E. coli, total and fecal coliforms as reported in many studies, the more recalcitrant the pathogen is, the higher doses of solar radiation and longer the exposure time will be required for its inactivation.…”
Section: Resistance Of Water Microorganismsmentioning
confidence: 99%